2015
DOI: 10.1007/s00572-015-0645-4
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of juvenile defoliation, light conditions, and interspecific competition on growth and ectomycorrhizal colonization of Fagus sylvatica and Pinus sylvestris seedlings

Abstract: Seedlings of forest tree species are exposed to a number of abiotic (organ loss or damage, light shortage) and biotic (interspecific competition) stress factors, which may lead to an inhibition of growth and reproduction and, eventually, to plant death. Growth of the host and its mycorrhizal symbiont is often closely linked, and hence, host damage may negatively affect the symbiont. We designed a pot experiment to study the response of light-demanding Pinus sylvestris and shade-tolerant Fagus sylvatica seedlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 68 publications
2
8
0
1
Order By: Relevance
“…After 10 years, dry root biomass was lesser decreasing than other parameters, probably due to the environmental selection in beech. The root system assures seedling survival exploring soil for water supply and nutrients, supporting mycorrhizal symbiosis [71]. Under a threshold related to the transpiring area (shoot) and to the water absorbing area (roots) the seedlings have no future.…”
Section: Effect Of Soil Compaction On Beech and Maple Seedlingmentioning
confidence: 99%
“…After 10 years, dry root biomass was lesser decreasing than other parameters, probably due to the environmental selection in beech. The root system assures seedling survival exploring soil for water supply and nutrients, supporting mycorrhizal symbiosis [71]. Under a threshold related to the transpiring area (shoot) and to the water absorbing area (roots) the seedlings have no future.…”
Section: Effect Of Soil Compaction On Beech and Maple Seedlingmentioning
confidence: 99%
“…Wargo [8,9] found that defoliation of trees can substantially decrease the starch content in the root wood and the sucrose levels in both bark and cambial tissues of sugar maple roots, which should decrease the attractiveness of these tissues for root pathogens. However, defoliation may also reduce the nutrition available to mycorrhizae and reduce their ability to contribute to water and nutrient uptake for the tree [10].…”
Section: Introductionmentioning
confidence: 99%
“…Barto & Rillig (2010), through a meta-analysis of 99 experiments from 33 publications, suggested that, in contrast with the carbon-limitation hypothesis, herbivory did not reduce mycorrhizal colonization by biologically significant levels in the majority of plants, including perennial grasses and forbs. Recently, Trocha et al (2015) have not found changes in the composition of ECM communities of Fagus sylvatica and Pinus sylvestris after damages, including defoliation. On the contrary, Markkola et al (2004) and Saravesi et al (2008) found changes in the ECM composition when Betula pubescens or P. sylvestris were defoliated, suggesting that high-biomass ECM fungal species need great quantities of carbon because they found a reduction of these fungi after defoliation.…”
Section: Effect Of Defoliation On Am Colonizationmentioning
confidence: 99%
“…Over long-term, leaf herbivory (and clipping) may eventually result in reduced carbon accessibility for the host plant and fungal partners (Barto & Rillig 2010, Saravesi et al 2014, although, in spite of the re-growth of the above-ground tissue, carbon allocation to roots often increases immediately after defoliation, while allocation to shoots decreases (Dyer et al 1991, Holland et al 1996. Although the impact of leaf herbivory on colonization by mycorrhizal fungi has mainly been reported as negative, sometimes even positive or nil effects on fungal symbiosis have been detected (Gehring & Whitham 1994, 2002, Cullings et al 2001, Eom et al 2001, Hokka et al 2004, Kula et al 2005, Pietikäinen et al 2005, Walling & Zabinski 2006, Gehring & Bennett 2009, Saravesi et al 2014, Trocha et al 2015. It has been reported that the variability in responses might depend on the type and extent of defoliation, the duration of the experiment, the mycorrhizal type or plant species considered, the availability of soil nutrients or other not yet known factors (Gehring & Whitham 2002, Gehring & Bennett 2009).…”
Section: Introductionmentioning
confidence: 99%